2012
DOI: 10.2215/cjn.06270611
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Cellular Immunity in Early Renal Artery Atherosclerosis

Abstract: SummaryBackground and objectives Modern imaging techniques have increased the incidental detection of renal atherosclerotic disease (RAD). Because immune activation may hasten RAD progression, identifying cellular immune markers might provide clues to clinical activity. In this study, cellular immune markers were assessed in early RAD.Design, setting, participants, & measurements Immune cell markers in peripheral blood of two groups of hypertensive patients with normal carotid and coronary arteries were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
(36 reference statements)
0
20
0
Order By: Relevance
“…Therefore, the pro-inflammatory/anti-inflammatory cytokines in monocyte/macrophage may play an important role in atherosclerosis of type 2 diabetic patients. Several lines of evidence suggest that circulating monocytes, precursors of macrophages, display heterogeneity in mice and humans, and its cell heterogeneity influences plaque formation and inflammatory phenotypes of macrophages in adipose tissue and atherosclerotic lesion [15][16][17][18][19]. Swirski FK et al also reported Ly-6C hi monocytes dominate hypercholesterolemia-associated monocytosis and give rise to macrophages in atheromata in mice [20].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the pro-inflammatory/anti-inflammatory cytokines in monocyte/macrophage may play an important role in atherosclerosis of type 2 diabetic patients. Several lines of evidence suggest that circulating monocytes, precursors of macrophages, display heterogeneity in mice and humans, and its cell heterogeneity influences plaque formation and inflammatory phenotypes of macrophages in adipose tissue and atherosclerotic lesion [15][16][17][18][19]. Swirski FK et al also reported Ly-6C hi monocytes dominate hypercholesterolemia-associated monocytosis and give rise to macrophages in atheromata in mice [20].…”
Section: Discussionmentioning
confidence: 99%
“…One must recognize, however, that atherosclerosis is a systemic disorder characterized by activation of multiple inflammatory pathways. Studies of vessels in patients with early ARVD indicate disturbances in both tissue and circulating inflammatory cell types, even before hypertension or parenchymal kidney injury are apparent (8). Recent studies also implicate immune mechanisms in driving experimental hypertension and its target manifestations (9).…”
Section: Vascular Occlusive Disease Affecting the Kidneymentioning
confidence: 99%
“…Studies in human atherosclerotic renovascular lesions indicate that subclinical lesions already have localization of inflammatory T-regulatory cells within vessel walls and modification of T cell-associated cytokine release even before reaching critical hemodynamic occlusion. 19 In other patients, segmental vascular occlusion is related to localized dissection and/or shelving of calcified debris that may be unrelated to inflammatory processes altogether. It should not be surprising that effects of large-vessel occlusive lesions may have widely variable effects on arterial pressure regulation and poststenotic processes within the kidney.…”
Section: Hemodynamics and The Focus On Blood Flowmentioning
confidence: 99%